Development of Communication in Children with Autism Spectrum Disorders in the United States and Russia - Esterbrook R.L; Esterbrook S.A; Dreyfus A.; Karpekova T.A; Soldatenkova E.N (Moscow State University of Psychology and Education, 2016)
The article presents an analysis of theoretical principles and methodological approaches within the framework of research schools both in the United States and Russia; these schools provide the basis for the development of effective learning and communication skills for children with Autism Spectrum Disorders (ASD). The authors consider the indicators for communication disorders in children with ASD, as well as the main strategies for overcoming them in the context of utilizing verbal behavior analysis (B.F. Skinner, M.L. Sundberg, J.W. Partington, and M.L. Barbera - USA), the tradition of cultural-historical psychology (L.S. Vygotsky, D.B. Elkonin, B.D. Elkonin - Russia), reflective-activity approach (A.N. Leontiev, V.K. Zaretsky - Russia), the theory of systemic dynamic localization of higher mental functions(A.R. Luria - Russia), and method of "replacing ontogenesis" (B.A. Arkhipov, A.V. Semenovich Russia). Despite the differences in methodologies used by American and Russian scholars, the most important idea is that the researchers and practitioners of both schools have common goal: to concentrate their efforts on developing social interaction skills in children with ASD, which helps them to better adjust in their lives and function in the social environment